2020
DOI: 10.1155/2020/9726261
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic Manifestations and Retinal Findings in Children with Down Syndrome

Abstract: Purpose. To evaluate ocular findings in children with Down syndrome and to compare with the healthy children group. Methods. The study patients were divided into two groups as the diagnosed Down syndrome group and the control group. The study was designed as a prospective and single-center study in Istanbul University Faculty of Medicine Department of Ophthalmology. The study included 93 patients in the age range from 7 to 18 years, who applied to the ophthalmology department of our clinic in the period from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
2
20
1
Order By: Relevance
“…The surgical techniques were adapted to each case, depending on the patient’s age, biometric measurements and associated eye anomalies. The chosen surgical treatment was related to the particularities of the children’s eyes: small antero-posterior axis, more curved cornea, special elasticity of the capsular bag, intense inflammatory response to surgical aggressions [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The surgical techniques were adapted to each case, depending on the patient’s age, biometric measurements and associated eye anomalies. The chosen surgical treatment was related to the particularities of the children’s eyes: small antero-posterior axis, more curved cornea, special elasticity of the capsular bag, intense inflammatory response to surgical aggressions [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we did not further investigate these retinal findings. However, Ugurlu and Altinkurt have found that individuals with trisomy 21 on average present with a higher central retinal thickness as well as higher retinal nerve fibre layer of the papilla [14]. Mangalesh et al showed that already infants with trisomy 21 can present with retinal abnormalities such as abnormal foveal morphology [15].…”
Section: Discussionmentioning
confidence: 99%
“…59 These findings are supported by other recent optical coherence tomography findings that children with Down syndrome have abnormal development of foveal morphology 60 or an increased retinal thickness. 61 Thus, mild foveal hypoplasia could contribute to decreased visual acuity and sensory nystagmus in some children with Down syndrome. Further, Laguna and colleagues and Ugurlu and colleagues, with the aid of optical coherence tomography, found increased thickness of the neural retina in individuals with Down syndrome as well as in the trisomic mouse model, probably due to genetic influences on retinal development.…”
Section: Nystagmusmentioning
confidence: 99%
“…Further, Laguna and colleagues and Ugurlu and colleagues, with the aid of optical coherence tomography, found increased thickness of the neural retina in individuals with Down syndrome as well as in the trisomic mouse model, probably due to genetic influences on retinal development. 61,62 Hypoaccommodation Accommodation is the capacity of the eye to change focus to enable clear vision at near. 26 Numerous studies have reported accommodation deficits in individuals with Down syndrome.…”
Section: Nystagmusmentioning
confidence: 99%